Social support, physical activity and sedentary behavior among 6th-grade girls: a cross-sectional study - Hoelscher Deanna M; Kelder Steven H; Springer Andrew E (BMC, 2006)
Abstract Background Despite the importance of social support in promoting physical activity, little is known about the relative influence of the type or source of social support on adolescent girls' physical activity and sedentary behaviors. This study examined the associations of two types of social support (social participation in and social encouragement for physical activity) and two social support sources (family and friends) with self-reported daily minutes of physical activity and sedentary behavior among sixth-grade girls in Texas. Methods A secondary analysis of 718 sixth-grade girls between the ages of 10 to 14 was performed using cross-sectional baseline data from an osteoporosis prevention intervention study. Physical activity and sedentary behaviors (television-video viewing and computer-video game playing) were assessed using 3 administrations of the Self-Administered Physical Activity Checklist; social support indicators were assessed with Likert-type items from a psychosocial questionnaire. Results In multiple linear regression analyses, friend physical activity participation (partial correlation coefficient (r) = 0.10, p = .009) and friend (r = 0.12) and family encouragement (r = 0.11) (p < .01, respectively) were positively related to moderate-to-vigorous physical activity in the full model with other support variables, BMI and ethnicity; friend encouragement was the only variable positively related to vigorous physical activity (r = 0.11, p = .005). Family participation in physical activity had the strongest negative correlation with total minutes of television-video viewing and computer-video playing (r = -0.08, p < .05). Conclusion Findings lend support to the importance of social support for physical activity among adolescent girls but suggest that the source and type of social support may differ for physical activity and sedentary behaviors. Further research is needed to assess the causal or reciprocal relation between the roles of friends and family in promoting physical activity and of family physical activity in decreasing sedentary behaviors among early adolescent girls.